Stylistic Analysis in William Shakespeare’s Selected Poem - Rizka Fauza Pasaribu; Wulan Safitri; Rahmadsyah Rangkuti (Prasasti: Journal of Linguistics, 2024)
This research aims to determine the language features in William Shakespeare's selected poems. In this research, the author used a descriptive qualitative approach as a research method. The theory used in analyzing William Shakespeare's selected novel is Geoffry Leech's theory for analyzing language levels which consist of phonological level, lexical level and semantical level. In this research, the author chose 2 of William Shakespeare's poems, entitled Sonnet 18 and Sonnet 29. Sonnet 18, contains the poet's admiration for someone. while sonnet 29 tells the story of someone who feels hopeless about his life, but because of love, he has the strength to live. This poem describes the impact of love on life.